Development of Augmented Reality Applications-Flat Geometry and Space in Android-Based Primary School - Widyaastuti, Eri; Rahmawati Suwanto, Fevi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This study aims to design an Android-based Flat and Spatial Geometry Augmented Reality Application in primary school (SD, Sekolah Dasar) that is valid and practical. This application uses the Vuforia library which is capable of playing sound and displaying animated 3D objects, played by the user in a real environment using the help of books and Android-based smartphones. This research is a Research and Development (R&D) study using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation) to develop Flat and Spatial Geometry Augmented Reality Applications in Elementary Schools as a learning medium that is expected to be able to create a fun and effective learning environment to improve students' mathematical literacy ability. The research subjects were 32 students of class VI at SD Negeri 050660 Kwala Bingai Stabat. The research instruments used in this study included validation sheets to obtain an assessment of the validity of the application, and student response questionnaires to determine the practicality of the application. The results of the research and development show that the Application of Augmented Reality Flat and Spatial Geometry is in very good criteria. The results obtained based on the analysis of the black box test obtained a success percentage of 100% and the white box test obtained a success percentage of 100%. While the average validation score is 90.19% of the total interpretation. In the field test, it was obtained an average practicality percentage of 84.5% from 15 assessment items. So that the application of augmented reality flat geometry and space is included in the very good criteria.